2014
DOI: 10.1016/j.cub.2014.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Plk4 Phosphorylates Ana2 to Trigger Sas6 Recruitment and Procentriole Formation

Abstract: SummaryCentrioles are 9-fold symmetrical structures at the core of centrosomes and base of cilia whose dysfunction has been linked to a wide range of inherited diseases and cancer [1]. Their duplication is regulated by a protein kinase of conserved structure, the C. elegans ZYG-1 or its Polo-like kinase 4 (Plk4) counterpart in other organisms [2–4]. Although Plk4’s centriolar partners and mechanisms that regulate its stability are known, its crucial substrates for centriole duplication have never been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
236
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 157 publications
(269 citation statements)
references
References 40 publications
17
236
0
Order By: Relevance
“…It has been suggested that recruitment of Asl onto the daughter centriole in Drosophila embryos occurs only once mother and daughter have separated at the end of mitosis and that this provides a duplication license (Novak et al 2014). However, it is notable that in cultured cells, the incorporation of Ana2 and Sas-6 onto the daughter's procentriole once it has disengaged from the mother in telophase appears to mark the very first event in the duplication process (Dzhindzhev et al 2014).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that recruitment of Asl onto the daughter centriole in Drosophila embryos occurs only once mother and daughter have separated at the end of mitosis and that this provides a duplication license (Novak et al 2014). However, it is notable that in cultured cells, the incorporation of Ana2 and Sas-6 onto the daughter's procentriole once it has disengaged from the mother in telophase appears to mark the very first event in the duplication process (Dzhindzhev et al 2014).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
“…Overexpression of STIL or Sas-6 in other systems leads to centriole overduplication (Kitagawa et al 2011a;Tang et al 2011;Arquint et al 2012;Vulprecht et al 2012). Both Ana2 and STIL localize to the innermost region of the centriole Dzhindzhev et al 2014), raising the possibility that Ana2/STIL might be part of the cartwheel structure. Indeed, the C. elegans SAS-5 physically binds a narrow central region of the SAS-6 coiled-coil domain, and is able to prevent the coiled-coil dimer from forming a tetramer in vitro (Qiao et al 2012).…”
Section: Martins Et Al 2007amentioning
confidence: 99%
See 3 more Smart Citations